Non-attendance of appointments at the orthodontic clinic - Au Carmen; Li Jingyi; Jin Liying; Wu Tianyou; Guan Guangzhao; Mei Li (Australasian Orthodontic Journal, 2024)
To investigate the non-attendance of patients at orthodontic appointments and to determine related reasons.